Removal of Chromium Ions from Tannery Wastewater using Cactus Powder - Salim, Hatim; Rimawi, waleed; Shaheen, Safa (Oriental Scientific Publishing Company, 2020)
Leather industry consumes large amounts of chemicals, particularly toxic chromium sulfate. 30-40% of chromium used in this industry is released as a solid or liquid waste, which eventually ends up in soil and ground water. This work aims at determining the total chromium in samples of tannery wastewater and removing it using Cactus as adsorbent. Detection of chromium (VI) and total chromium was performed spectrophotometricaly using 1.5-diphenylcarbazide reagent in addition to diazo-coupling reaction (between sulphanilic acid and N, N-dimethylaniline). The efficiency of removing Chromium ions from contaminated tannery wastewater by adsorption on cactus powder was investigated by batch experiments and the effects of various parameters (pH, adsorbent dosage and treatment time) on the percentage removal of chromium were investigated. The percentage removal obtained was 98.8% for chromium (VI) and 97.0% for chromium (III) at optimum conditions: pH = 8, adsorbent dosage equal 6.0 g/l and contact time of 60 min. The results of this work demonstrated for first time that removing chromium ions, especially carcinogenic chromium (VI), using cactus powder is more efficient than commonly used calcium carbonate.
Keywords: Adsorption; Cactus; Tannery Wastewater; Total Chromium.